Too good to be true : the rise and fall of Bernie Madoff - Arvedlund, Erin (New York : Portfolio, 2009)
Discusses the multi-billion dollar financial scheme masterminded by Bernard Madoff, detailing the history of his business practices and who else was involved in the scheme.
Includes bibliographical references (pages 283-299) and index.
Keywords: Madoff, Bernard L; Swindlers and swindling -- United States -- Biography; Ponzi schemes -- United States